Development of an Interactive Module Based on Socio-Scientific Issues (SSI) to Improve Students' Scientific Literacy - Puspitarini, Bety Indri; Widodo, Wahono; Suprapto, Nadi (International Journal of Emerging Research and Review, 2025)
Objective: This study aims to develop and evaluate an interactive module based on Socio-Scientific Issues (SSI) to improve science literacy among sixth-grade elementary students. Specifically, the objectives are to create a valid, practical, and effective learning module, to assess its impact on students’ critical thinking and scientific discussion skills, and to compare the learning outcomes between experimental and control groups. Method: This study employed a development research design to create an interactive module based on Socio-Scientific Issues for sixth-grade science learning. Validation was conducted through expert reviews on content and media aspects. Practicality was tested by involving teachers and media experts. Effectiveness was measured using a quasi-experimental design with pretest-posttest control group, analyzing learning outcomes through statistical tests. Results: The developed interactive module based on Socio-Scientific Issues was validated with an average expert score of 89%, indicating its suitability for use in science learning. Practicality tests with teachers and media experts yielded a score of 90%, confirming the module’s ease of use. Effectiveness analysis showed a significant difference between the experimental and control groups (p = 0.000), with the experimental group demonstrating higher learning outcomes and improved science literacy skills. Novelty: This study introduces an innovative interactive module integrating socio-scientific issues to enhance science literacy in elementary students. Unlike conventional modules, it emphasizes critical thinking and real-life scientific debates, supported by validated content and media, making it both practical and effective in diverse classroom settings.